STRATEGI PROMOSI KEGIATAN DUTA PERADILAN MAHKAMAH AGUNG UNTUK MENARIK ATTENTION PUBLIK - Kurniati, Ifah Atur; Widyowati, Ratih (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The activities of the Supreme Court Judicial Ambassadors aim to strengthen relations between the law and the younger generation. The nation's next generation must have a deep understanding of the law to form a civilized society and reduce legal problems among youth. Through promotion and publication using the third party endorsement method and the AIDA formula, the Supreme Court tries to reach the public effectively. This research uses a qualitative approach to evaluate the impact of the promotion. This promotional effort was successful in attracting public attention and building trust and sympathy for this government institution. This is important in strengthening the foundation of legal understanding among the younger generation and forming a more legally aware society as well as narrowing the gap in legal knowledge among young people